Pendampingan Pengembangan Sistem Informasi AMI Berbasis PPEPP dengan Vibe Coding pada Program Studi Informatika UNIM - Ahmad Syaifuddin; Ronny Makhfuddin Akbar; Hafizh Fianto Putra; Yanuarini Nur Sukmaningtiyas; Anita (Universitas Dirgantara Marsekal Suryadarma, 2026)
Implementing the Internal Quality Assurance System (SPMI) via the PPEPP cycle is a mandatory requirement for study programs to align with LAM INFOKOM accreditation criteria. The assessment process is often hindered by the management of the Self-Evaluation Report (LED) and Internal Quality Audit (AMI) documentation, which still rely on manual, conventional filing methods. To address these issues, this community service initiative was organized to assist the quality assurance team in designing an integrated management information platform. The innovative approach adopted for this software development is